Gondang Sabangunan sebagai Pengiring Sigale-Gale untuk Menarik Wisatawan di Museum Huta Bolon Kecamatan Simanindo - Ruth Olivia Sirait; Pulumun Petrus Ginting; wiflihani wiflihani (Mahesa Research Center, 2021)
This study aims to determine the Gondang Sabangunan performance in accompanying Sigale-gale at the Huta Bolon Museum for packaging tourism performances, impact and government support. The method in this study uses a qualitative descriptive method. The speakers in this study were employees of the Huta Bolon Simanindo Museum, 5 music players, 10 dancers, Simanindo community leaders, and tourists. The data was collected by means of observation, interviews, documentation and literature study. The results showed that the development of cultural tourism through the Gondang Sabangunan performance that accompanied Sigale-gale which is a cultural attraction to attract tourists at the Huta Bolon Simanindo Museum. The tortordi performance of the Huta Bolon Simanindo Museum was held on an open stage in the old village of Huta Bolon. Performances are not sacred but still follow the customary rules of the nigondang such as the number of types of gondang, the rules for requesting the type of gondang, the rules for movement in tortor, clothes and equipment. Another packaging of the show form is the short and dense duration, full of variations, an imitation of the original form. Tourists can enjoy the potential of Batak Toba culture, such as music, dances, historical objects, and the nuances of the Toba Batak village.